Kesalahan Konstruksi Konsep Mahasiswa pada Materi Himpunan dan Defragmentasi Struktur Berpikirnya - Latifah Mustofa Lestyanto; Syaiful Hamzah Nasution; Ety Tejo Dwi Cahyowati; Muhammad Shohibul Kahfi (JRPM (Jurnal Review Pembelajaran Matematika), 2019)
This research was conducted to identify errors in the construction of concepts and to know the form of defragmentation of students’ thinking structures on set material. Data collection was done by asking students to answer on the main test questions. Data were analyzed by data reduction, data presentation, and conclusion. The results of the research indicate that the errors in the construction of mathematical concepts of students on set material were: 1) pseudo-constructions in the form of true pseudo and false pseudo, 2) misconstruction, 3) misconnection, and 4) logical thinking errors. The forms of defragmentation or the process of rearranging the thinking structures of students who experience concept construction errors in the set were conducted by giving scaffolding and cognitive conflict.